ECONOMIC OPPORTUNITIES AND SOCIAL RESPONSIBILITY IN THE MODERN GAMBLING INDUSTRY - Mykhailov, Stanislav (Український економічний часопис, 2024)
Introduction. The gambling industry plays a significant role in national economies, contributing to revenue generation, job creation, and tax income. However, it poses challenges related to regulation and social costs, such as addiction and financial distress among vulnerable populations. Technological advancements, including AI and blockchain, are reshaping the industry, presenting both opportunities and regulatory complexities. Purpose. This study aims to analyze the economic impact, regulatory frameworks, social implications, and technological advancements in the gambling industry. The research focuses on understanding how these factors interact and shape the future of the sector, with the goal of providing insights for policymakers on balancing economic gains with social responsibility. Results. The findings highlight that while the gambling industry supports economic growth and benefits from technological innovations, it also amplifies risks of problem gambling and social harm. Effective regulatory models, such as targeted interventions and responsible gambling measures, are crucial for minimizing these risks. The analysis emphasizes the importance of evidence-based policies that adapt to the rapidly evolving landscape of the gambling industry. Conclusions. A sustainable gambling industry requires a holistic approach that aligns economic benefits with social accountability. Policymakers must prioritize harm reduction strategies, responsible gambling practices, and adaptive regulations to ensure that the industry's growth does not come at the expense of societal well-being. This study offers a comprehensive overview for stakeholders seeking to navigate the complexities of the modern gambling sector.